“Resi-Property” as a Complaint-Platform of Mobile Application System - Abdul Nasim, Muhammad Faris (IRC, 2019)
Living under the same roof in a high-rise property is known as a jointly owned property with common ownership with other multiple house units’ owners. Sharing the facilities and areas would have been a common practice for residents that sometimes need a proper monitoring. When it comes to incidents or complaints reporting which never been easy when it involves many parties in. The development of Resi-Property as mobile application in a cross-platform availability will help to simplify the day-to-day tasks when it comes to reporting, resolving and getting updates from the management. This development has been initiated by observing the inefficient of common flow process while taking up the roles as managing property in one of the property management company. At the end of the development, prototype will be tested by the real clients in order to get the real feedback and validation for future work or enhancement.